Bumble bees of North America : an identification guide - Williams, Paul (Paul Hugh) (Princeton University Press, 2014)
This guide allows amateur and professional naturalists to identify all 46 bumble bee species found north of Mexico and to understand their ecology and changing geographic distributions.